PROGRAM KEMITRAAN KELOMPOK PENGURUS DESA "POLAMANKU" TENTANG PENCEGAHAN PENULARAN VIRUS CORONA - Ristanto, Riki (Jurnal EMPATI (Edukasi Masyarakat, Pengabdian dan Bakti), 2021)
Dukuh Polaman Desa Bedali Kecamatan Lawang Kabupaten Malang is a tourist village known as "Polamanku". The variety of existing tourist infrastructure has the potential to become a gathering place for visitors, especially during holidays, but these facilities and infrastructure have not been facilitated by hygiene facilities, especially for the prevention of the corona virus contagious disease (covid-19). The purpose of this community service activity is to increase the knowledge and skills of partners regarding the management of prevention and control of the corona virus (covid-19). This community service is carried out through the method of seminars, mentoring, and procurement of tools for partners. This community service was attended by 15 administrators of the "Polamanku" tourism village. The target output of community service that has been achieved is in the form of services and products. Services in this case are in the form of providing seminars on management of prevention of transmission of the corona virus (covid-19) as well as assistance on the use of thermogun, 6 steps to wash hands, and use of masks. Through this method it is proven to be able to increase partners' understanding of the corona virus (covid-19) and the prevention of transmission (100%). The products that have been produced are in the form of banners and hand washing tools as a means of supporting the sustainability of the corona virus (covid-19) transmission prevention program. It is hoped that this activity can be sustainable independently carried out by partners and can inspire other similar tourism vehicles, considering that these activities have not been carried out a lot.